PERLINDUNGAN HUKUM TERHADAP SOPIR JASA EKSPEDISI YANG BEKERJA PADA PERUSAHAAN CV(COMMANDITAIRE VENNOOTSCHAP) DI KOTA DUMAI - Rahma, Waliyul; Deliana, Evi; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Legal protection of labor is undertaken to ensure harmonious employment withoutany pressure from other stronger party. In Act Number 13 of 2003 on Manpower,there is a normative guarantee of the rights of the wholesale workers but is notimplementation and difficult to implement which in the reality there are stilloffenses that occured while the law enforcement was unclear, the scope of workwhich the legal protections still unclear is to the driver of the expedition service in the city of Dumai. The problems in this study were formulated: (1) How is the legal form of the driver of the expedition service in the city of Dumai? (2) What is the inhibiting factor for legal protection for expedition service drivers in the city of Dumai?.This research was conducted through sociologis and empirical approach withprimary data, secondary data and tertiary data, which each data obtained fromlibrary research and field. Qualitative design was applied in this research toanalyse the data.Implementation of legislation that exists or runs is still far from what is expected, for this reason the supervision of the supervisor of the authorized agency is expected to work optimally so that protection for workers and is achieved according to its objectives.Keywords: Legal Protection, Employment, Expedition Services Driver, Company